(untitled) (Journal of Hama University, 2019)
This study was carried out on ninety (90) one-day old unsexed one of the commercial crossed of broiler chicken were used in this experiment which lasted for 45 days. This study which aimed to study the effect of adding different levels of Vitamin C in drinking water in some Biochemical Parameters Broiler Chickens by Heat stress. The chicks were randomly distributed into three groups each contained( 30) chicks. three groups were used as follows : G1 Control No vitamin c added , G2 Adding 150mg vitamin cwater , G3Adding 200mg vitamin cwater , feed and water were Ad Libitum . The results showed the significant increase (P <0.05) in the level of the total protein in the additive groupsG2,G3 when they were compared with the control group G1in the age35-45 days. And there were decrease significant(P <0.05) in the total cholesterol level in the additive groupsG2,G3 comparision with the group G1in the age35-45 days.